UPAYA PENINGKATAN KOGNITIF ANAK USIA DINI MELALUI BERMAIN ISTANA PASIR DI TK ABA TEGALREJO BANTUL - Bagus Mahardika (STPI Bina Insan Mulia Yogyakarta, 2020)
This study aims to determine the implementation of playing sand castles in early childhood and to improve cognitive aspects of early childhood through playing sand castles in Kindergarten ‘Aisyiyah Bustanul Athfal Tegalrejo Bantul. Indicators of achieving cognitive aspects in this study are children can recognize the size, color and shape of objects through playing sand castles. This research is a type of classroom action research (CAR) which consists of two cycles with four stages, namely planning, implementation, observation and reflection. The first cycle consisted of two meetings, and the second cycle consisted of two meetings. The subjects of this study were students in TK ABA Tegalrejo Bantul with a total of 17 students. Data collection techniques using interviews, observation and documentation. Data analysis techniques using qualitative descriptive analysis. The results showed that: children's understanding in recognizing the color, size and shape of objects through playing sand castles increased from cycle I to cycle II. Based on observations on pre-action CAR, the success rate of learning to use sand castle play is very significant where the percentage before the action of cognitive ability to recognize the color, size and shape of objects of learners in group A is 29.4%. After the action is increased in cycle 1 by 47.06% so the cognitive improvement of students from before the action up to the first cycle increased by 17.66% and in the second cycle increased to 94.11%. So cognitive improvement from cycle I to cycle II increased to 47.05%. The cognitive improvement of students through playing sand castle increased by 64.71%. The results achieved showed that students more easily recognize the color, size and shape of objects through playing sand castle.